IDIC Implementation Process - Rizky, Miftahur (Journal of Renewable Engineering, 2024)
Amidst increasingly tight business competition and increasingly critical customers in choosing products or services, companies are required to build more personal and sustainable relationships through Customer Relationship Management (CRM) strategies. The IDIC (Identify, Differentiate, Interact, Customize) model developed by Peppers and Rogers is one of the effective approaches in implementing CRM in a structured and strategic manner. This study aims to analyze the application of the IDIC Model in improving the effectiveness of customer relationship management. The approach used is qualitative with descriptive-analytical methods, through literature studies and literature analysis from various relevant sources. The results of the discussion show that the IDIC Model facilitates companies to recognize customers comprehensively, differentiate them based on value and needs, build meaningful interactions, and customize offers individually. Identify and Interact are included in the operational CRM realm, while Differentiate and Customize are part of analytical CRM that relies on customer data analysis. This model enables large-scale personalization, which is strengthened by big data technology and artificial intelligence (AI), so that companies can increase customer engagement, loyalty, and business profits sustainably. The application of the IDIC Model reflects a shift from mass marketing to a more relevant one-to-one marketing approach in the digital era